Biological Effect of Crude Alkaloid Extract of Cordia Myxa L. Leaves on Some Stages of Musca Domestica (Diptera: Muscidae) - Jabbar Mohammed Al-Bahadyli, Layla; Naeem Atia, Afrah (International Journal of Psychosocial Rehabilitation, 2020)
Objective: We found from the present study the effect of alkaloid extract of Cordia myxa on some stages of Musca domestica (third instar larvae and pupa with 24h and 72h). The results showed that leaves affected performance in some stages of Musca domestica and increased distortion numbers for treatments (third instar larvae and pupa with 24h and 72h) compared to the control treatment. Also, results showed the death of all naturally emerging insects for all treatments compared to the control treatment. Methods: The alkaloid extract tested against larvae and pupae of Musca domestica the efficacy test was achieved at different concentrations (2.5, 5, 7.5 and mg/ml) The Results: results showed differences in treatments of third instar larvae and pupae with ages of 24h and 72h. Also showed results increased numbers of distortions for larvae and pupa compared to control treatment. Conclusion: The results described in this study show that the alkaloid extract showed distortions and differences in treatments (direct spray for larvae, spray pupae at age 24 h and 72 h). The best concentration in alkaloid extract was 10 mg/ml. The best treatments in alkaloid extract were the treatment of pupa with age 24h, in concentration 10 mg/ml, and varied mortality rates of larvae and pupa to all treatments and to all concentrations.